Petrological and geochemical comparison of the ultramafic rocks of Tulppio, Jänesselkä and Värriöjoki, eastern Finnish Lapland - Haapala, Pieti (Helsingin yliopisto, 2019)
Komatiites are extrusive rocks crystallized from mantle derived high-MgO magmas. They formed mainly during the Archean as the required high degree partial melting of the mantle peridotite (>20%) was facilitated by the geotherm of that time. Komatiites are classified as volcanic rocks with >18 wt.% MgO and <1 wt. % TiO2. By their physical features komatiite melts are of high-temperature and low-viscosity. Komatiitic rock suites are abundant in the Archean bedrock of the eastern Finnish Lapland. They are mainly found as cumulate bodies with also their related komatiitic basalts and mafic volcanic rocks being abundant in the Tulppio Metavolcanic belt. Typical of Archean terrains in Fennoscandia, all komatiitic rocks in the eastern Lapland are extensively deformed and primary mineral assemblages and textures are rare. Mapping and sampling was performed in the municipalities of Savukoski and Salla, NE Finland, in order to clarify the geochemical characteristics and petrogenesis of the komatiitic suites of the Eastern Lapland Archean Domain (ELAD). On the basis of their lithology and previous studies, three komatiitic cumulate complexes were selected for detailed geochemical and petrographical comparison. These are the Jänesselkä mafic-ultramafic complex, the Tulppio ultramafic complex, also referred to as the Tulppio dunite, and the Värriöjoki ultramafic complex. The first two are situated in the Tulppio metavolcanic belt whereas the Tuntsa metasedimentary belt hosts the Värriöjoki ultramafic complex. The lithology and geochemical characteristics of the Jänesselkä mafic-ultramafic complex suggest it having a different origin than the komatiitic rocks forming the Tulppio metavolcanic belt. Based on parental magma calculation and near continuum of rock types observed the Jänesselkä mafic-ultramafic complex represents a fractionated magma chamber with a basaltic composition (~6 wt. % MgO). The dunitic Värriöjoki ultramafic-complex is a feeder cumulate formed from a magma with a composition of high-MgO basalt ...